2014
DOI: 10.1016/j.tecto.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Relative impact of mantle densification and eclogitization of slabs on subduction dynamics: A numerical thermodynamic/thermokinematic investigation of metamorphic density evolution

Abstract: Understanding the relationships between density and spatio-thermal variations at convergent plate boundaries is important for deciphering the present-day dynamics and evolution of subduction zones. In particular, the interaction between densification due to mineralogical phase transitions and slab pull forces is subject to ongoing investigations. We have developed a two-dimensional subduction zone model that is based on thermodynamic equilibrium assemblage calculations and includes the effects of melting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 96 publications
1
18
0
Order By: Relevance
“…In our zircon dating results, the peak of 162-168 Ma may represent the initial subduction of the BangongNujiang suture zone, because numerous models and observations have shown that old and cold oceanic lithosphere becomes denser than the underlying asthenosphere (Capitanio et al, 2010;Duesterhoeft et al, 2014;Marques et al, 2013;Oxburgh and Parmentier, 1977;Uyeda and Kanamori, 1979), and when the oceanic crust is first subducted, the additional dragging force associated with the cold and dense oceanic plate will decrease the pressure of the magma chambers in the mid ocean ridge, which in turn product larger amounts of mafic magma than usual. This inference is also supported by regional geological data.…”
Section: Genesis Of the Zircons Within The Oceanic Islands And Ophiolmentioning
confidence: 86%
“…In our zircon dating results, the peak of 162-168 Ma may represent the initial subduction of the BangongNujiang suture zone, because numerous models and observations have shown that old and cold oceanic lithosphere becomes denser than the underlying asthenosphere (Capitanio et al, 2010;Duesterhoeft et al, 2014;Marques et al, 2013;Oxburgh and Parmentier, 1977;Uyeda and Kanamori, 1979), and when the oceanic crust is first subducted, the additional dragging force associated with the cold and dense oceanic plate will decrease the pressure of the magma chambers in the mid ocean ridge, which in turn product larger amounts of mafic magma than usual. This inference is also supported by regional geological data.…”
Section: Genesis Of the Zircons Within The Oceanic Islands And Ophiolmentioning
confidence: 86%
“…The deformation of materials is accommodated via an elastoviscoplastic rheology, which self‐consistently reproduces diverse deformation processes like faulting, flexure, and lower crustal flow. SLIM3D has been extensively benchmarked and applied to model lithospheric‐scale processes in divergent [ Brune et al , , ; Brune and Autin , ; Brune , ; Heine and Brune , ; Koopmann et al , ; Clift et al , ; Brune et al , , ], convergent [ Quinteros et al , ; Quinteros and Sobolev , ; Duesterhoeft et al , ], and transform [ Popov et al , ; Brune , ] plate boundaries and in a centimeter‐scale study of localization dynamics [ Cyprych et al , ].…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The free-energy minimization can be carried out in two ways: by dynamic or by static implementation. Dynamic implementation means minimizing the Gibbs free-energy of the system at a particular value of pressure, temperature, and composition during the 10.1029/2018JB016032 inversion process (e.g., Afonso et al, 2013;Chust et al, 2017;Duesterhoeft & Capitani, 2013;Duesterhoeft et al, 2014;Khan et al, 2006). Alternatively in the static implementation, physical properties are calculated for a certain range of pressure-temperature conditions and stored in tables prior to the solution of the inverse problem (e.g., Zunino et al, 2011).…”
Section: Computation Of Mantle Mineral Phase Equilibriamentioning
confidence: 99%